Baltimore. Volume one, The plague ships - Mignola, Michael; Golden, Christopher; Stenbeck, Ben.; Stewart, Dave. (Milwaukee, Ore. : Dark Horse Books, 2011)
"After a devastating plague ends World War I, Europe is suddenly flooded with vampires. Lord Henry Baltimore, a soldier determined to wipe out the monsters, fights his way through bloody battlefields, ruined plague ships, exploding zeppelins, and submarine graveyards, on the hunt for the creature who's become his obsession."--Jacket flap.
"Collects the Baltimore: The Plague Ships comic-book series, issues 1-5, published by Dark Horse Comics"--T.p. verso.
Keywords: Vampires -- Comic books, strips, etc; Soldiers -- Comic books, strips, etc; Horror comic books, strips, etc; Graphic novels